En visite chez les vieux‑croyants d’Estonie orientale - Léonard, Ksenija Djordjević; Léonard, Jean Léo (Études finno-ougriennes, 2019)
L’article porte sur une expérience de terrain réalisée en Estonie orientale, en avril 2018. Notre objectif était d’explorer la question de l’intégration nationale, mais aussi transnationale, à travers des enquêtes qualitatives sur les représentations de l’identité nationale, sociolinguistique et religieuse d’un secteur de la composante russophone de la population estonienne et, partant, européenne : la communauté des vieux‑croyants de la rive occidentale du lac Peïpous, où elle s’est implantée à la fin du xviie siècle, en rupture avec la réforme du rite orthodoxe de Russie. Nous relaterons ici cette expérience en trois étapes : la préparation du terrain, le séjour sur place, et nos premières conclusions sur cette situation qui nous semble exemplaire d’une intégration équilibrée, dans un monde traversé par des crises et des conflits. We present here a summary of a recent fieldwork experience, carried out in April 2018, in Eastern Estonian, on the Western shore of Lake Peipus. Through interviews of artists, scholars and cultural activists working for the promotion of the Old Believers’ cultural heritage, we attempted to fathom the identity and insights of this sector of Estonian population, within the framework of Estonian nation‑building and European integration. Old Believers split from Reformist Orthodoxy at the middle of the Seventeenth Century, in Russia. Among many communities of Old Believers who fled persecutions worldwide, one settled on the Western shore of the Peipus lake, in Estonia – under Swedish rule at that time. The account of our sociolinguistic empirical inquiry is threefold: (i) preliminary contacts and planning of the expedition, (ii) the documentary work carried out on the spot, and (iii) some considerations on how this case study on Old Believers’ cultural movement in Estonia contributes to both a theory and a praxis of multicultural integration. Such insights are all the more relevant nowadays, in a period of sociocultural instability and geopolitical crisis worldwide. В статье ...